Differential regulation of the glucose-6-phosphatase TATA box by intestine-specific homeodomain proteins CDX1 and CDX2 - Gautier-Stein, Amandine (Oxford University Press, 2003)
Glucose-6-phosphatase (Glc6Pase), the last enzyme of gluconeogenesis, is only expressed in the liver, kidney and small intestine. The expression of the Glc6Pase gene exhibits marked specificities in the three tissues in various situations, but the molecular basis of the tissue specificity is not known. The presence of a consensus binding site of CDX proteins in the minimal Glc6Pase gene promoter has led us to consider the hypothesis that these intestine-specific CDX factors could be involved in the Glc6Pase-specific expression in the small intestine. We first show that the Glc6Pase promoter is active in both hepatic HepG2 and intestinal CaCo2 cells. Using gel shift mobility assay, mutagenesis and competition experiments, we show that both CDX1 and CDX2 can bind the minimal promoter, but only CDX1 can transactivate it. Consistently, intestinal IEC6 cells stably overexpressing CDX1 exhibit induced expression of the Glc6Pase protein. We demonstrate that a TATAAAA sequence, located in position –31/–25 relating to the transcription start site, exhibits separable functions in the preinitiation of transcription and the transactivation by CDX1. Disruption of this site dramatically suppresses both basal transcription and the CDX1 effect. The latter may be restored by inserting a couple of CDX- binding sites in opposite orientation similar to that found in the sucrase-isomaltase promoter. We also report that the specific stimulatory effect of CDX1 on the Glc6Pase TATA-box, compared to CDX2, is related to the fact that CDX1, but not CDX2, can interact with the TATA-binding protein. Together, these data strongly suggest that CDX proteins could play a crucial role in the specific expression of the Glc6Pase gene in the small intestine. They also suggest that CDX transactivation might be essential for intestine gene expression, irrespective of the presence of a functional TATA box.